Dynamics of the Bingham Canyon rock avalanches (Utah, USA) resolved from topographic, seismic, and infrasound data. Issue 3 (16th March 2017) - Moore, Jeffrey R.; Pankow, Kristine L.; Ford, Sean R.; Koper, Keith D.; Hale, J. Mark; Aaron, Jordan; Larsen, Chris F.
Abstract: The 2013 Bingham Canyon Mine rock avalanches represent one of the largest cumulative landslide events in recorded U.S. history and provide a unique opportunity to test remote analysis techniques for landslide characterization. Here we combine aerial photogrammetry surveying, topographic reconstruction, numerical runout modeling, and analysis of broadband seismic and infrasound data to extract salient details of the dynamics and evolution of the multiphase landslide event. Our results reveal a cumulative intact rock source volume of 52 Mm 3, which mobilized in two main rock avalanche phases separated by 1.5 h. We estimate that the first rock avalanche had 1.5–2 times greater volume than the second. Each failure initiated by sliding along a gently dipping (21°), highly persistent basal fault before transitioning to a rock avalanche and spilling into the inner pit. The trajectory and duration of the two rock avalanches were reconstructed using runout modeling and independent force history inversion of intermediate‐period (10–50 s) seismic data. Intermediate‐ and shorter‐period (1–50 s) seismic data were sensitive to intervals of mass redirection and constrained finer details of the individual slide dynamics. Back projecting short‐period (0.2–1 s) seismic energy, we located the two rock avalanches within 2 and 4 km of the mine. Further analysis of infrasound and seismic data revealed that the cumulative event included an additional 11 smaller landslides (volumes ~10 4 –10 5  m 3 ) and that a trailing signal following the second rock avalanche may result from an air‐coupled Rayleigh wave. Our results demonstrate new and refined techniques for detailed remote characterization of the dynamics and evolution of large landslides. Key Points: Cumulative 52 Mm 3 mass movement consisted of two large rock avalanches and at least 11 smaller landslides Broadband seismoacoustic data reveal slide volumes and trajectories as well as finer‐scale dynamics Combined analyses provided complementary results allowing more powerful joint interpretation